THE ANALYSIS OF DETERMINANT OF FOREIGN DIRECT INVESTMENT IN INDONESIA - Etsuco Siomi; Wawan Hermawan (Quantitative Economics Journal, 2019)
The analysis results show that changes in macroeconomic conditions such as exchange rate, government expenditure and gross domestic product in Indonesia have a significant effect on foreign direct investment (FDI) Indonesia, while Inflation has a negative effect on foreign direct investment FDI and the monetary crisis has a negative effect on the development of FDI in Indonesia. So that the severe financial crisis in the American and European regions today, the impact on foreign direct investment (FDI) Indonesia is still within the limits of tolerance. Therefore, although there are still problems in the investment climate in Indonesia, the outlook for investment in Indonesia over the next period is still good, although perhaps with the growth of investment slows down.